Strategi pemerintah daerah dan masyarakat dalam pengembangan kampung adat tutubhada sebagai desa wisata di kabupaten nagekeo provinsi nusa tenggara timur - Melang, Yosep Kristianus; Widyatmaja, I Gusti Ngurah; Rahyuda, Irma (Jurnal Kepariwisataan dan Hospitalitas, 2019)
STRATEGI PEMERINTAH DAERAH DAN MASYARAKAT DALAM PENGEMBANGAN KAMPUNG ADAT TUTUBHADA SEBAGAI DESA WISATA DI KABUPATEN NAGEKEO PROVINSI NUSA TENGGARA TIMUR Yosep Kristianus Melang 1) ,  I Gusti Ngurah Widyatmaja, S.ST.Par, M.Par 2) , Irma Rahyuda, A.Par., MM., M.Par., M.Rech 3 ) Program Studi Diploma IV Pariwisata, Fakultas pariwisata, Universitas Udayana, Jl. Dr. Goris Nomor 7 Denpasar, Bali 80232. Telp/Faks : (0361) 223798, E-mail : infopariwisata@unud.ac.id/fakultaspariwisata.unud@yahoo.com ABSTRACT   Faculty of Tourism Study Program Diploma IV Tourism Udayana University Final Project   Name                                  :     Yosep Kristianus Melang Title                                    :     The strategic of the local government with the society in developing the Tutubhada Traditional Village as a tourist village in Nagekeo regency, East Nusa Tenggara Province   Number of pages             :     20 (Ilustration : Table ) Summary content             : This research is based on the many tourism potentials that are owned by Nagekeo Regency, East Nusa Tenggara Province. The  Government and society are required to be able to strategic in tourism development including the development of tourism villages. The purpose of this study was to describe and analyze the implementation of strategic, strength factors and weaknesses of strategic, as well as the results of strategic in carrying out the development of the Tutubhada traditional village as a Tourism Village. The results of the study were expected to provide advice or recommendations to the government and the public regarding the synergy pattern of development. This study used a qualitative descriptive research method. The research used qualitative data and quantitative data as well as primary data and secondary data. Data collection method used is interview method, observation and literature study. The strategic of the local government and the society in implementing the development of the Tutubhada traditional village as a tourist village was successful, judging from the pattern of implementers, programs, and facilities and infrastructure. This synergy turned out to bring positive results on the value and social change of the Tutubhada society, as well as success in developing tourism potential. The driving factor is the content of regulations that are easy to understand, the attitude of the community in applying synergy principles and regulatory provisions. The inhibiting factor is human resource capacity, and the budgeting process is not balanced. Overall with the many limitations that are owned, the government and the society continue to make every effort to realize tourism development. Important to note in the development of the Tutubhada traditional village as a tourism village in the future is to pay attention to the synergistic coordination.   Keywords: Strategic pattern, Government and society, tourism villages